ISSUES OF MULTICULTURAL EDUCATION OF FUTURE TEACHERS BASED ON THE AXIOLOGICAL APPROACH (EDUCATION IN THE 21ST CENTURY, 2023)
The development of modern world society is characterized by globalization, which has affected all spheres of human life. It has led to the intensification of ties in various fields: economics, culture, education, etc. Increasing globalization brings with it many social problems, contradictions, conflicts of various types, cultural and value differences, which are sometimes alien to our cultural and value ideas. Under these conditions, it is especially difficult for young people, whose life experience and value system are not very stable yet. Help can be provided to them through the education system as a whole, and especially in the process of multicultural education.The problem of multicultural education is very relevant in Pedagogy. An analysis of scientific research on the problem showed that various approaches were used to solve the problems of multicultural education, for example, ethnological, systemic, etc. But consideration of issues of multicultural education based on the axiological approach has almost been not studied.The given article is part of a study on the multicultural education issues of future teachers based on the axiological approach. This part of the study examines the essence, purpose, principles, functions, content, forms and methods, results of multicultural education within the framework of the axiological approach, the use of which increases the effectiveness of this education.The result of the study of the given problem was a theoretical model of multicultural education with a value position, which will contribute to the effective solution of problems of multicultural education of students of pedagogical specialties in the context of globalization, the formation of value behavior in the context of diverse cultures based on the value system of future teachers.The presented work is a theoretical part of the study on this issue, which assumes further experimental approbation of the model and its further improvement; development of an approximate work plan for multicultural education of students with pedagogical specialties; conducting seminars with lecturers of the Department of Pedagogy of SUSh on the issue under study.
Keywords: globalization; multiculturalism; multicultural education; values; axiological approach; model of multicultural education